Early Administration of Apelin Could Prevent Heart Failure Following Myocardial Injury; A Systematic Review and Meta-Analysis - Hasheminezhad, Mohammad-Mehdi; Mirzad, Mina; Sepehry Vafa, Saeed; Moradi, Amir-Reza; Mahdavi, Nastaran Sadat; Azizi, Yaser; Yousefifard, Mahmoud (Archives of Academic Emergency Medicine, 2024)
Introduction: Heart failure (HF) is a prevalent and advancing cardiovascular disorder that impacts 1-2% of the worldwide population, particularly the elderly. Studies indicate that the intravenous administration of apelin may yield advantageous effects in preventing heart failure subsequent to myocardial injury. This meta-analysis aimed to assess the effects of exogenous apelin administration on heart failure in animal models, in light of the lack of a definitive consensus on the matter. Method: An extensive search was performed in the Medline (via PubMed), Web of Science, Embase, and Scopus databases till the end of January 2024. Two independent reviewers screened and summarized the relevant articles. Outcomes related to cardiac function, including ejection fraction (EF), maximum and minimum rate of left ventricle systolic pressure (+dp/dt and –dp/dt, respectively), heart rate, left ventricular end-diastolic pressure (LVEDP), and left ventricular systolic pressure (LVSP) were assessed. Findings were reported as a pooled standardized mean difference (SMD) with a 95% confidence interval (95% CI). Results: 12 studies were included. Pooled analysis demonstrated that early treatment with apelin following myocardial injury significantly increases +dp/dt (SMD = 2.36; 95% CI: 1.58 to 3.15; p < 0.001) and decreases -dp/dt (SMD = -3.31; 95% CI: -4.46 to -2.17; p < 0.001). Furthermore, the administration of apelin resulted in a significant increase in EF (SMD = 0.79; 95% CI: 0.15 to 1.44; p = 0.02) and LVSP (SMD = 2.09; 95% CI: 0.82 to 3.36; p < 0.001), while it led to a decrease in LVEDP in the animals (SMD = -1.85; 95% CI: -2.81 to -0.88; p < 0.001). Noteworthy, apelin treatment was shown to have no significant influence on the heart rate of the animals (SMD = -0.12; 95% CI: -0.82 to -0.58; p = 0.73). Conclusion: The current study demonstrated that the early administration of apelin has the potential to improve cardiac function and mitigate the onset of heart failure subsequent to myocardial injury. Further, in vivo research is essential to lay the groundwork for the integration of apelin into clinical practice.